Penerapan Metode VIKOR Untuk Seleksi Guru Terbaik Pada SMP Muhammadiyah 7 Semarang - Wakhidah, Nur; Mufrodah, Ismi (Universitas Semarang, 2022)
The teacher is one of the professional educators who has the duties, functions and important roles in educating the life of the nation. The predicate of the best teacher is one way to improve the quality of the quality of education in SMP Muhammadiyah 7 Semarang. SMP Muhammadiyah 7 Semarang is a private status school which is under the auspices of the Muhammadiyah Regional Leadership (PDM) Semarang Primary Education Council (Dikdasmen). Process The determination of the best teacher at SMP Muhammadiyah 7 Semarang is still based on subjectivity of decision making, so it is not transparent. Therefore, researchers built a decision support system that can help calculate the appropriateness of the best teacher at SMP Muhammadiyah 7 Semarang with the Hypertext Preprocessing (PHP) programming language using the Vise Kriterijumska Optimizacija I Kompromisno Resenje method. The criteria used are work discipline, teacher absenteeism, work ability, duties and responsibilities, additional activities, and personality. Based on the test results, the system that was built can help the SMP Muhammadiyah 7 Semarang in making decisions to determine the teacher achievement objectively, quickly and accurately without requiring a long time in its calculations.